2008
DOI: 10.1016/s0049-3848(08)70009-4
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIIa binding to endothelial cell protein C receptor

Abstract: Recent studies have shown that factor VIIa (FVIIa) binds specifically to endothelial protein C receptor (EPCR), a known cellular receptor for protein C and activated protein C, on the endothelium. The formation of FVIIa:EPCR complexes neither supports the activation of coagulation nor modulates tissue factor-initiated coagulation. However, FVIIa interaction with EPCR, particularly at pharmacological concentrations of FVIIa, may impair EPCR-dependent protein C activation and activated protein C-mediated cell si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In addition, EPCR functions as a receptor for coagulation factors VIIa (68,(71)(72)(73) and Xa (74). EPCR-FVIIa interactions may sequester FVIIa from procoagulant phosphatidylserine-rich membrane domains, thereby exerting a FVIIa-dependent anticoagulant activity (73,75), and modulate the bioavailability of therapeutically administered recombinant FVIIa (76).…”
Section: Epcrmentioning
confidence: 99%
“…In addition, EPCR functions as a receptor for coagulation factors VIIa (68,(71)(72)(73) and Xa (74). EPCR-FVIIa interactions may sequester FVIIa from procoagulant phosphatidylserine-rich membrane domains, thereby exerting a FVIIa-dependent anticoagulant activity (73,75), and modulate the bioavailability of therapeutically administered recombinant FVIIa (76).…”
Section: Epcrmentioning
confidence: 99%
“…Also in rats, histopathological examinations of the liver suggest that rFVIIa is cleared by hepatocytes and kuppfer cells via clathrin-mediated endocytosis [11]. Recent data suggest that rFVIIa associates with the vascular endothelium, specifically with the endothelial cell protein C receptor (EPCR) [12], and perhaps enters into the extravascular space [13]; however, the clinical significance of these findings is not clear as the amount and the activity status is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although many cellular studies have investigated the fate of rFVIIa both in the presence and absence of TF (5)(6)(7)(8)(9), the mechanisms of rFVIIa clearance and metabolism following intravenous (iv) administration have not been extensively studied. Whole body autoradiography and tissue distribution studies in which radioiodinated rFVIIa ( 125 I-rFVIIa) was administered intravenously to rats showed that radioactivity was associated with a few highly perfused organs, including the liver (10,11).…”
Section: Introductionmentioning
confidence: 99%